Genetic diversity of multidrug resistant Salmonella enterica subsp. enterica serovar Brancaster isolated from chicken in Malaysia - Khoo, Evie; Roslee, Roseliza; Zakaria, Zunita; Ahmad, Nur Indah (Malaysian Society for Molecular Biology and Biotechnology, 2023)
Salmonella enterica subsp. enterica serovar Brancaster is a chicken-associated serovar that is increasingly reported in the Asian region, including Malaysia. The shortfall of conventional serovar identification for nomenclature alone is insufficient for studying the genetic and clonal relationships of Salmonella of the same serovar. Whereas DNA sequence-based typing method is useful to study the genetic diversity and relatedness of the highly diverse Salmonella. In this study, the genetic diversity, phenotypic antimicrobial resistance (AMR) profiles, and detection of selected AMR genes from ten representative Salmonella Brancaster isolates from chicken cloacal swabs and raw chicken meat were carried out. Based on multilocus sequence typing (MLST), all Salmonella Brancaster belonged to sequence type ST2133. Further analysis of the MLST sequencing data using concatenated nucleotide sequences of the seven housekeeping genes divided them into nine clusters, revealed heterogeneity and genetic diversity among the isolates. All isolates were multidrug-resistant (MDR), which confers resistance to three or more classes of antibiotics. Seven Salmonella Brancaster isolates exhibited phenotypic ACSSuT-type MDR profile, and two of them were also resistant towards ciprofloxacin. Salmonella Brancaster in the present study possessed at least one and up to six resistance genes, with the most prevalent being the ampicillin (blaTEM), tetracycline (tetA), chloramphenicol (floR), gentamicin (ant(3”)-Ia), streptomycin (strA), and sulfonamides (sul-2). Chickens are common reservoir for serovar Brancaster and the emergence, persistence, and dissemination of MDR Salmonella Brancaster possessed a public health risk. The authorities need to strengthen salmonellosis control management programme in poultry farms, abattoirs, and processing facilities.